Insights on the extraction performance of Alkanediols and Glycerol: ssing Juglans regia L. Leaves as a source of bioactive compounds - Vieira, Vanessa (2018)
Glycerol and alkanediols are being studied as alternative solvents to extract phytochemicals from plant material, often as hydrogen bond donors in deep eutectic solvents (DESs). Many of those alcohols are liquid at room temperature, yet studies of their use as extraction solvents are scarce. In this work, glycerol and a series of alkanediols (1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,2-pentanediol, 1,5-pentanediol, and 1,2-hexanediol) were studied for the extraction of phenolic compounds from Juglans regia L. leaves, a rich source of this class of bioactive compounds. The extraction yield was quantified, and the bioactivity of both extracts and pure solvents was evaluated by measuring the anti-inflammatory and cytotoxic activities. The solvents showing the best combined results were 1,2 and 1,3-propanediol, as their extracts presented a high amount of phenolic compounds, close to the results of ethanol, and similar cytotoxicity against cervical carcinoma cells, with no impact on non-tumor porcine liver cells in the studied concentration range. On the other hand, none of the extracts (and solvents) presented anti-inflammatory activity. Overall, the results obtained in this work contribute to the study of alternative solvents that could potentially be used also as formulation media, highlighting the importance of walnut leaves as a source of bioactive compounds.